Implementasi Model Belajar Problem Based Learning untuk Meningkatkan Hasil Belajar Materi Gaya di Sekitar Kita Mata Pelajaran IPAS Kelas 4 SDN Mojoroto 1 - Wahyuni, Rika; Novitasari, Aprilia; Khusnaini, Faridhotuz Zulfa; Hidayah, Nurul; Yuliana, Siti; Mutmainah, Siti; Nurmilawati, Mumun (Jurnal Simki Postgraduate, 2024)
Low scientific literacy occurs in students at SDN Mojoroto 1. The cause is also the same as the general problems that occur in Indonesia. Based on this, a learning approach is needed that can improve students' abilities optimally, both in cognitive, affective, and psychomotor aspects. One approach that is considered effective in improving student learning outcomes is Problem-Based Learning (PBL). This study uses PTK (Classroom Action Research). The application of the Problem Based Learning (PBL) learning model to fourth grade students of SDN Mojoroto 1 significantly improves learning outcomes. This is indicated by an increase in the average student score from cycle I of 28.3 to 53.1 in cycle II, and finally reaching 84.8 in cycle III, with a percentage increase in learning outcomes between cycles of 24.8% and 31.7%. The N-gain test which obtained a percentage of 78.2% showed that the PBL model was in the effective category. This success was strengthened through reflection and improvement from the previous cycle, which made the implementation of PBL in cycle II more optimal with a success rate of 100%. The PBL model has been proven to improve student understanding, activeness in learning, and critical thinking skills.